2021
DOI: 10.1088/1361-6579/abdf3b
|View full text |Cite
|
Sign up to set email alerts
|

A 4D flow cardiovascular magnetic resonance study of flow asymmetry and haemodynamic quantity correlations in the pulmonary artery

Abstract: Objective. In this paper we elucidate the asymmetric flow pattern and the haemodynamic quantity distributions and correlations in the pulmonary artery (PA) vasculature in healthy adults having structurally normal hearts, to provide reference on the flow characteristics in the PA and the right ventricle. Approach. Velocity data are acquired non-invasively from 18 healthy volunteers by 4D flow magnetic resonance imaging, resolved to 20 phases with spatial resolution 3 × 3 × 3 mm3. Interpolation is applied to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous studies have shown the utility of 4D flowderived vorticity metrics which has been associated with inefficient blood flow in patients with pulmonary [12,14,15,[20][21][22][23] and aortic disease [13,16]. Although qualitative vortices and swirling has been associated with diseased states [13,22], our study shows global quantitative metrics of vorticity increasing post-PEA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Previous studies have shown the utility of 4D flowderived vorticity metrics which has been associated with inefficient blood flow in patients with pulmonary [12,14,15,[20][21][22][23] and aortic disease [13,16]. Although qualitative vortices and swirling has been associated with diseased states [13,22], our study shows global quantitative metrics of vorticity increasing post-PEA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have shown correlations between non-invasive 4D flow CMR-derived velocity profiles and invasively measured PA pressures, as well as changes in the peak velocities after surgical correction in patients with CTEPH [4,6,[9][10][11]. Complex secondary flow structures such as vortical flow, where fluid rotates around an axis, and helical flow, where fluid rotates and moves in one direction in a cork-screw motion with clockwise (positive) or counterclockwise (negative) rotation, have been characterized with 4D flow CMRs of major vessels in healthy and diseased PAs and aortas, such as PH and bicuspid aortic valve disease [12][13][14]. Vorticity and recirculation of flow have been associated with inefficient blood flow and diseased states in the PAs and aorta [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, changes in pressure may precede changes in other hemodynamic parameters of the pulmonary artery, resulting in it being the most important indicator in early remodeling of the pulmonary circulation. Furthermore, MPA and RPA might be more susceptible to exercise compared with LPA 33 . This susceptibility may be attributed to the asymmetrical flow distribution in pulmonary arteries, as the RPA has a larger diameter, higher peak stroke velocity and higher rotational energy intensity than the LPA 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MPA and RPA might be more susceptible to exercise compared with LPA. 33 This susceptibility may be attributed to the asymmetrical flow distribution in pulmonary arteries, as the RPA has a larger diameter, higher peak stroke velocity and higher rotational energy intensity than the LPA. 22,23 Consequently, RPmax of MPA-RPA was the most sensitive factor for identifying CR and/or MF, highlighting its potential importance in assessing early remodeling of the pulmonary circulation.…”
Section: The Value Of ML For Identifying Cr And/or Mf In Athletesmentioning
confidence: 99%